If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying d + -12 = 22 Reorder the terms: -12 + d = 22 Solving -12 + d = 22 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + d = 22 + 12 Combine like terms: -12 + 12 = 0 0 + d = 22 + 12 d = 22 + 12 Combine like terms: 22 + 12 = 34 d = 34 Simplifying d = 34
| 274-7x=38+19 | | 5u^2-5u-100=0 | | 2+(3+m)= | | p/2+5=45 | | 5(8j)= | | 8x+14=-138 | | 4x+2+3x= | | s+0.45=10.07 | | 6x+10=140-9x | | 3(5n)= | | x-1/3-x-2/5=x+1/8 | | g/3+6=18 | | 2+(3+z)= | | x^2-10x-1=-8x+2 | | -3x-7x=-70 | | 3x+x+5x=2700 | | .3(4b-2)=-6+12b | | m/4+6=70 | | 2.7b=8.37 | | f/13=25 | | -123=d+81 | | -5x-25=-10 | | 10(8+b)=80 | | x^2-11x+29=0 | | 21=j/27 | | 2h-18=28 | | (x+y+3)(x+y-4)=0 | | v+742=750 | | -8=v/19 | | v+42=99 | | 3m-12=18 | | 80=f+18 |